A Survey of Digital Literacy among Students of Foundation Studies in Management: A Case Study in Public Higher Institution Malaysia - Md Yusof, Zahayu; Misiran, Masnita; Lim Qing, Jun; Goh Hong, Quan; Sobri, Anis Hanisah; Mahmud, Nur Athirah (Universiti Pendidikan Sultan Idris, 2023)
The ability to navigate the digital world using reading, writing, technical skills, and critical thinking together with the ability to discover, evaluate, utilize, share, and create content using information technologies is called digital literacy. Access to the Internet has increased from time to time. This showed that technology has infiltrated into our daily lives and encouraged more processes to become data-driven and virtual. This study used descriptive statistical methods to determine the digital literacy level among Foundation Studies in Management students. This study also identified reasons why students engage in digital technologies. The findings showed that female students tend to spend more hours on their cell phones and computers. Most of the student in Foundation Studies in Management responded with moderate-high agreement on their level of digital literacy, which means that most of them understand and can apply simple and fundamental computer knowledge for personal purposes and academic matters